Seeking the proper sphere (and scope) of public deliberation - Sekerak, Marian (Civilia, 2015)
There is a broad consensus among the leading theorists on the fact that the current representative democracy is experiencing a major crisis. Nowadays, the concept of what may be called New Elitism becomes more and more popular, especially among the younger generation. This concept recalls in its consequences upon Plato's idea of an ideal state governed by well-trained and skilled philosophers. Against the government of "enlightened" authorities I postulate the concept of deliberative democracy. Firstly, I briefly introduce the possibility of deliberative innovations in parliament; however I consider them as insufficient and vague. Secondly, I try to clarify the concept of representation in deliberation, particularly through the civic associations. My research on civic deliberation in practice is based on the analytical interview with a participant and organizer of participatory and deliberative activities in the Slovak capital city Bratislava. At the end of my paper I conclude that the authorities, politicians and scholars should play only an advisory and supportive role in deliberation. I strongly oppose to the so-called Pure Proceduralists and argue that deliberation without definite conclusions and collectively binding decisions is a weak deliberation. Moreover, I try to point out the fact that civic associations do not meet the conditions of accountability and legitimacy; they always represent only a part of the public.
Keywords: Deliberative democracy; Participatory democracy; Representation; Civic associations